2018
DOI: 10.1186/s12986-018-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Green cardamom increases Sirtuin-1 and reduces inflammation in overweight or obese patients with non-alcoholic fatty liver disease: a double-blind randomized placebo-controlled clinical trial

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is the hepatic component of metabolic syndrome. Despite the beneficial health effects of cardamom on dyslipidemia, hepatomegaly, and fasting hyperglycemia, no previous human study has been conducted on the efficacy of cardamom in NAFLD. The aim of this study was to assess the effects of green cardamom (GC) on serum Sirtuin-1 (Sirt1), inflammatory factors, and liver enzymes in overweight or obese NAFLD patients.MethodsThe recruitment of subjects was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 72 publications
2
32
0
1
Order By: Relevance
“…Spices and their bioactive compounds are also beneficial to FLD patients. Several double-blind randomized placebo-controlled clinical trials showed that the intake of 500 mg of green cardamom 3 times per day for 3 months could decrease the degree of fatty liver in NAFLD patients, accompanied by decreasing the levels of ALT, CRP, TNF- α , and IL-6, as well as increasing the serum level of SIRT1 [ 159 ]. Besides, the intake of 70 mg per day of curcumin for 8 weeks significantly reduced fatty liver in NAFLD patients, accompanied by improving the serum levels of liver enzymes, lipid profiles, glucose, and glycated hemoglobin [ 160 ].…”
Section: Clinical Trials Of Plant-based Foods and Their Bioactive mentioning
confidence: 99%
“…Spices and their bioactive compounds are also beneficial to FLD patients. Several double-blind randomized placebo-controlled clinical trials showed that the intake of 500 mg of green cardamom 3 times per day for 3 months could decrease the degree of fatty liver in NAFLD patients, accompanied by decreasing the levels of ALT, CRP, TNF- α , and IL-6, as well as increasing the serum level of SIRT1 [ 159 ]. Besides, the intake of 70 mg per day of curcumin for 8 weeks significantly reduced fatty liver in NAFLD patients, accompanied by improving the serum levels of liver enzymes, lipid profiles, glucose, and glycated hemoglobin [ 160 ].…”
Section: Clinical Trials Of Plant-based Foods and Their Bioactive mentioning
confidence: 99%
“…TNF-α is a pro-inflammatory biomarkers which is abundantly produced in adipose tissue macrophages. (Figure 4) High level of TNF-α increase dyslipidemia, insulin resistance, and secretion of IL-6 [24,25]. High levels of this cytokine cause proliferation of theca intra cells, which leads to hyperplasia and an increase number of the follicles.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6r gene maps to human chromosome 1q21 in which is responsible of IL-6 production [26]. IL-6 is an endocrine inflammatory cytokine that produced in many body cells for example adipose tissue in acute and chronic inflammation [24]. High excess IL-6 level was associated with obesity, insulin resistance, hyperandrogenism, and ovarian dysfunction [25,1,5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the decrease in LDL-c was significant in the unadjusted model and showed a trend in the adjusted model. Based on our previous findings in the other part of this trial [ 59 ], compared with placebo, GC significantly diminished serum alanine transaminase (ALT) by 127% and heightened Sirtuin 1 (Sirt1) by 40% ( P < 0.05). In addition, the fall in BMI showed a trend among GC group in comparison with the placebo group.…”
Section: Discussionmentioning
confidence: 99%